(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2026)
This study explores the influence of international university rankings on university management in Latin America. The objective is to identify and analyze the main indicators used in these rankings and their impact on strategic decisions. A theoretical review methodology was employed to explore the relationship between the indicators and university management. The results, derived from a systematic analysis of key ranking indicators and their documented impact on university strategic decisions, reveal the specific areas where these indicators exert substantial influence on institutional reputation and global positioning, particularly within the Latin American context. The study concludes by emphasizing the critical consideration of ranking indicators and by providing recommendations for strategic decision-making in Latin American universities aimed at targeted improvements in areas such as research quality, internationalization, and talent attraction, thereby contributing to the advancement of knowledge in the field of higher education in the region.